Multiple independent IgE epitopes on the highly allergenic grass pollen allergen Phl p 5. Issue 11 (November 2014) - Levin, M.; Rotthus, S.; Wendel, S.; Najafi, N.; Källström, E.; Focke‐Tejkl, M.; Valenta, R.; Flicker, S.; Ohlin, M.
Summary Background Group 5 allergens are small proteins that consist of two domains. They belong to the most potent respiratory allergens. Objective To determine the binding sites and to study allergic patients' IgE recognition of the group 5 allergen (Phl p 5) from timothy grass pollen using human monoclonal IgE antibodies that have been isolated from grass pollen allergic patients. Methods Using recombinant isoallergens, fragments, mutants and synthetic peptides of Phl p 5, as well as peptide‐specific antibodies, the interaction of recombinant human monoclonal IgE and Phl p 5 was studied using direct binding and blocking assays. Cross‐reactivity of monoclonal IgE with group 5 allergens in several grasses was studied and inhibition experiments with patients' polyclonal IgE were performed. Results Monoclonal human IgE showed extensive cross‐reactivity with group 5 allergens in several grasses. Despite its small size of 29 kDa, four independent epitope clusters on isoallergen Phl p 5.0101, two in each domain, were recognized by human IgE. Isoallergen Phl p 5.0201 carried two of these epitopes. Inhibition studies with allergic patients' polyclonal IgE suggest the presence of additional IgE epitopes on Phl p 5. Conclusions & Clinical Relevance Our results reveal the presence of a large number of independent IgE epitopes on the Phl p 5 allergen explaining the high allergenic activity of this protein and its ability to induce severe allergic symptoms. High‐density IgE recognition may be a general feature of many potent allergens and form a basis for the development of improved diagnostic and therapeutic procedures in allergic disease.